2020
DOI: 10.5852/ejt.2020.680
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Swedish species of Neoxorides Clément, 1938 (Ichneumonidae: Poemeniinae) with the description of a new species and an illustrated key to species

Abstract: Neoxorides Clément, 1938 is a small genus of ichneumonid wasps that develop on wood-boring beetles. We here revise the Western Palaearctic species of the genus, with a special focus on Sweden. A new species, N. striatus Johansson sp. nov. is described. Neoxorides opacus (Kokujev, 1903) stat. rev. is excluded from the synonymy with N. nitens (Gravenhorst, 1829) and reinstated as a valid species. The species is redescribed from European material. Neoxorides kissi (Ulbricht, 1911) is confirmed as a junior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 668 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Furthermore, there might be habitat types that have not been covered extensively by SMTP (Johansson 2020), hence additional sampling might be necessary to complete the faunistic records for this genus. This result lends support to other studies that showed major knowledge gaps for parasitoid wasps and Diptera, even in the faunistic record of well-studied countries such as Sweden (Johansson and Cederberg 2019;Johansson 2020;Johansson and Klopfstein 2020;Riedel 2020;Ronquist et al 2020). Several of the newly recorded species were restricted to southern and coastal areas (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, there might be habitat types that have not been covered extensively by SMTP (Johansson 2020), hence additional sampling might be necessary to complete the faunistic records for this genus. This result lends support to other studies that showed major knowledge gaps for parasitoid wasps and Diptera, even in the faunistic record of well-studied countries such as Sweden (Johansson and Cederberg 2019;Johansson 2020;Johansson and Klopfstein 2020;Riedel 2020;Ronquist et al 2020). Several of the newly recorded species were restricted to southern and coastal areas (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The PCRs for CAD were run at an annealing temperature of 52 °C. Two additional internal primers for degenerated COI sequences were used; forward FA336 and reverse RA435 (Johansson and Klopfstein 2020), these primers were combined with LCO/HCO and run on an annealing temperature at 50 °C. The quality of the PCR products was then checked on a 2% agarose electrophoresis gel and they were sent for cleanup and sequencing to Macrogen Europe in the Netherlands.…”
Section: Laboratory Protocolmentioning
confidence: 99%
“…se/). The faunistic provinces included were Lycksele Lappmark, Norrbotten, Pite Lappmark, Västerbotten, Ångermanland, and Åsele Lappmark (Johansson and Klopfstein 2020). Based on herbarium records, 79 species representing 25 genera had been collected in these six northernmost provinces.…”
Section: Initial Selection Criteriamentioning
confidence: 99%
“…Poemeniinae and Xoridinae are relatively small subfamilies of the Darwin wasps (Hymenoptera, Ichneumonidae) represented in Europe by 13 and 50 species, respectively (Kasparyan, 1981;Yu et al, 2016;Johansson & Klopfstein, 2020;Johansson, 2022;Johansson et al, 2022). Th e representatives of both subfamilies are recorded mainly as idiobiont ectoparasitoids of saproxylic coleopterans and hymenopterans (Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Poemeniines and xoridines are among the best studied ichneumonid groups in both Poland and Ukraine, with 8 and 31 species (Hilszczanski, 2002;Bogdanowicz et al, 2007), and 11 and 30 species (Varga, 2015 a, b;Johansson & Klopfstein, 2020), respectively.…”
Section: Introductionmentioning
confidence: 99%